Peningkatan Pengetahuan Ibu Hamil Terhadap Pemberian ASI Eksklusif di Desa Saradan Kecamatan Karangmalang: Peningkatan Pengetahuan Ibu Hamil Terhadap Pemberian ASI Eksklusif di Desa Saradan Kecamatan Karangmalang - afri, kriska; Heni Hirawati Pranoto; Agnes Bien; Yunita Santi Lalo; Indah Nurmala Sari (Universitas Ngudi Waluyo, 2022)
Based on Basic Health Research (RISKESDAS) 2021 data, exclusive breastfeeding coverage data has decreased by 12% from the rate of achievement of exclusive breastfeeding in 2019. Around 52.5% or half of 2.3 million babies aged less than six months are getting exclusive breastfeeding in Indonesia. ASI. Exclusive is breastfeeding only in infants up to 6 months of age without additional fluids or food. Exclusive breastfeeding for 6 months is recommended by international guidelines which are based on scientific evidence about the benefits of breastfeeding for both the baby, the mother, the family and the country (WHO, 2011). Mother's knowledge about exclusive breastfeeding is very influential on the practice of exclusive breastfeeding. Lack of mother's knowledge about the benefits of exclusive breastfeeding can lead to additional feeding which results in mothers not giving exclusive breastfeeding to babies (Faradila, et al, 2021). The results of Refi Lindawati's research (2019) show that there is a relationship between knowledge and the success of exclusive breastfeeding. Mothers who have good knowledge are proven to give exclusive breastfeeding more than mothers who have poor knowledge. Mothers with poor knowledge say that they do not understand the importance of exclusive breastfeeding for the baby's health so they are not motivated to provide exclusive breastfeeding to their babies. There is a relationship between mother's knowledge about lactation management and the success of exclusive breastfeeding (Hutagaol, 2018). to increase the knowledge of pregnant women as early as possible about the benefits of exclusive breastfeeding so that pregnant women can prepare themselves for the breastfeeding process later. community service activities are carried out in three stages. The first stage is introduction and filling out the pre-test questionnaire. The second stage was conducting counseling about the benefits of exclusive breastfeeding for infants with lecture, discussion and question and answer methods using power point media (PPT) and posters. The third stage is filling out the post-test questionnaire and evaluating knowledge and evaluating the questionnaire. after conducting counseling about the benefits of exclusive breastfeeding, post-test data obtained from 7 pregnant women showed an increase in correct answers. 7 pregnant women (100%) understand the benefits of exclusive breastfeeding. Abstrak berdasarkan data Riset Kesehatan Dasar (RISKESDAS) 2021 menyebutkan data cakupan ASI Eksklusif menurun 12% dari angka pencapaian ASI Eksklusif di tahun 2019. Sekitar 52,5% atau setengah dari 2,3 juta bayi berusia kurang dari enam bulan yang mendapatkan ASI eksklusif di Indonesia.ASI. Eksklusif adalah pemberian ASI saja pada bayi sampai usia 6 bulan tanpa tambahan cairan ataupun makanan. Pemberian ASI eksklusif selama 6 bulan dianjurkan oleh pedoman internasional yang didasarkan pada bukti ilmiah tentang manfaat ASI baik bagi bayi, ibu, keluarga, maupun Negara (WHO, 2011). Pengetahuan ibu tentang ASI Eksklusif sangat berpengaruh pada praktik pemberian ASI Eksklusif. Kurangnya pengetahuan ibu tentang manfaat pemberian ASI Eksklusif dapat menyebabkan pemberian makanan tambahan yang mengakibatkan ibu tidak memberikan ASI Eksklusif pada bayi (Faradila, dkk, 2021). Hasil penelitian Refi Lindawati (2019) menunjukkan bahwa terdapat hubungan pengetahuan dengan keberhasilan pemberian ASI eksklusif. Ibu yang memiliki pengetahuan baik terbukti memberikan ASI eksklusif lebih banyak dibandingkan dengan ibu yang berpengetahuan kurang baik. Ibu dengan pengetahuan kurang baik mengatakan bahwa tidak mengerti pentingnya ASI Eksklusif bagi kesehatan bayi sehingga tidak termotivasi untuk memberikan ASI eksklusif kepada bayinya Terdapat hubungan antara pengetahuan ibu tentang manajemen laktasi terhadap keberhasilan pemberian ASI Eksklusif (Hutagaol, 2018). untuk meningkatkan pengetahuan ibu hamil sedini mungkin tentang manfaat pemberian ASI Eksklusif sehingga ibu hamil dapat mempersiapkan diri untuk proses menyusui nanti. kegiatan pengabdian masyarakat dilakukan dalam tiga tahap. Tahap pertama perkenalan dan pengisian kuesioner pre-test. Tahap kedua melakukan penyuluhan tentang manfaat pemberian ASI Eksklusif pada bayi dengan metode ceramah, diskusi dan tanya jawab menggunakan media power point (PPT) dan poster. Tahap ketiga pengisian kusioner pos-test dan melakukan evaluasi pengetahuan serta evaluasi kuesioner. setelah dilakukan penyuluhan tentang manfaat pemberian ASI Eksklusif didapatkan data post-test 7 ibu hamil yang menunjukkan adanya peningkatan jawaban benar. 7 ibu hamil (100%) memahami tentang manfaat pemberian ASI Eksklusif.